The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5755/j01.erem.77.3.28493
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Bioelectricity from Organic Fruit Waste

Abstract: This research proposes an alternative for companies and farmers through the production of electricity using microbial fuel cells (MFCs) using waste from export products. Nine MFCs were manufactured with zinc and copper electrodes; and as substrates, pineapple, potato and tomato pulp wastes were used in the anode chamber, and residual sludge in the cathode chamber. It was observed that the MFCs with pineapple substrate generated higher values of the electrical parameters, resulting in voltage and current values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Figure 2a shows the voltage values obtained from the MFC-SC during the 12 days of monitoring, observing an increase in the values from the first day in the MFC-SC of the Target (0.08 V) and cell with P. stutzeri (0.12 V) until the sixth, where they reached their maximum values of 0.35 and 0.91 V, respectively, and then observed a decrease in values until the last day (0.17 and 0.15 V). The literature has reported that the increase in voltage values in the first few days is due to the oxidation-reduction process between the chambers due to a large amount of organic matter [27,28]. In contrast, the decrease in potential values is inevitable because the metabolism of the microorganisms is obtained through the oxidation of the substrate used, which is depleted [29,30].…”
Section: Results and Analysismentioning
confidence: 99%
“…Figure 2a shows the voltage values obtained from the MFC-SC during the 12 days of monitoring, observing an increase in the values from the first day in the MFC-SC of the Target (0.08 V) and cell with P. stutzeri (0.12 V) until the sixth, where they reached their maximum values of 0.35 and 0.91 V, respectively, and then observed a decrease in values until the last day (0.17 and 0.15 V). The literature has reported that the increase in voltage values in the first few days is due to the oxidation-reduction process between the chambers due to a large amount of organic matter [27,28]. In contrast, the decrease in potential values is inevitable because the metabolism of the microorganisms is obtained through the oxidation of the substrate used, which is depleted [29,30].…”
Section: Results and Analysismentioning
confidence: 99%
“…This technology has different types of design, but it basically consists of two chambers (anodic and cathodic) almost always joined by a proton exchange membrane inside, where the electrodes (anodic and cathodic) that are inside the chambers meet. They are joined on the outside by an external circuit [23,24]. MFCs use chemical energy to convert it into electrical energy, mainly due to the oxidation and reduction processes that occur [25].…”
Section: Introductionmentioning
confidence: 99%